2020
DOI: 10.3389/fimmu.2020.00885
|View full text |Cite
|
Sign up to set email alerts
|

Information and Emotional Support Needs of Families Whose Infant Was Diagnosed With SCID Through Newborn Screening

Abstract: Background: Now that severe combined immune deficiency (SCID) has been added to newborn screening panels in all 50 states in the U.S., there is a need to develop and disseminate well-designed educational materials to parents who need information to make informed decisions about treatment and care for identified infants. SCID Compass was designed to address this gap. We summarize the results of two needs assessment activities for parents-a journey mapping exercise and online survey-which will inform the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Included studies used methodologies such as quantitative (n=15), 1,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] qualitative (n=22), 10, and mixed methodology (n=4) [56][57][58][59] or review (n=1). 60 The majority of studies were conducted in the United States (US) (n=23), 1,23,24,28,29,[32][33][34][35]37,[39][40][41]43,45,47,48,50,52,53,56,58,60 followed by Australia (n=6), 27,38,42,51,54,55 Canada (n=4) 10,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies used methodologies such as quantitative (n=15), 1,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] qualitative (n=22), 10, and mixed methodology (n=4) [56][57][58][59] or review (n=1). 60 The majority of studies were conducted in the United States (US) (n=23), 1,23,24,28,29,[32][33][34][35]37,[39][40][41]43,45,47,48,50,52,53,56,58,60 followed by Australia (n=6), 27,38,42,51,54,55 Canada (n=4) 10,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies included only mothers, 10,32,40,[46][47][48]51 one study included only fathers 50 and 19 included both parents and/or caregivers. 1,21,24,26,30,31,33,35,36,42,44,45,49,53,54,[56][57][58][59] In asking what are the patterns of parental use of social media to find health information for their children are, our review discovered the majority of quantitative studies of large social media platforms found that parents made extensive use of Facebook (10% to 100%) 1,[21][22][23][24][25][26][27][28][29][30][32][33][34][57][58][59][60] to access health information. Parents also commonly used Twitter (0.8% to 42.9%), 21,23,24,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This paper reveals opportunities to enhance the SCID NBS system by expanding communication pathways and educational outreach and establishing more formal long-term follow-up. As SCID NBS programs and treatments evolve, continued knowledge dissemination regarding lessons learned will further enable programs like SCID Compass to enhance linkages between families and services and to further elaborate long-term follow-up strategies for infants identified through NBS (15).…”
Section: Resultsmentioning
confidence: 99%
“…An important issue is the choice of tactics to inform parents about the positive results of screening. Studies in the United States have shown that families with children with SCID diagnosed by newborn screening experience certain emotional and other challenges at various stages of diagnosis and treatment, from screening and diagnosis to treatment options and prolonged isolation 38 .…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Compass web site was proposed, which contains useful and important information that can help parents overcome stress and uncertainty at different stages of diagnosis and treatment 38 .…”
Section: Prospects Of Newborn Screening For Pidmentioning
confidence: 99%